Identification of Potential High-Risk Patients on the Basis of PROMs in a Certified Centre for Joint Replacement (EndoProthetikZentrum) Using the Example of Hip Arthroplasty - Osmanski-Zenk, Katrin; Klinder, Annett; Ellenrieder, Martin; Darowski, Martin; Goosmann, Martin; Mittelmeier, Wolfram (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background In addition to clinical parameters, the subjective assessment by the patient to evaluate the operative outcome of an arthroplasty is becoming increasingly important. Questionnaires are used to identify patients who have not achieved the treatment goal at an early stage so that further interventions can be indicated.Material and Methods A questionnaire consisting of different PROMs was completed pre- and 3 months postoperatively by patients who had been treated with a hip arthroplasty. A standardised follow-up examination of these patients was carried out 12 to 16 weeks postoperatively, after which it was determined whether further therapy was necessary to achieve the treatment goal. Different consequences were defined for this.Results Significant differences were found between the groups of consequences of follow-up examinations over both time points, but also when postoperative scores were considered exclusively. Furthermore, the correlations for the postoperative scores and some consequences of the clinical follow-up for the Oxford Hip Score (OHS), the OHS functional score and the Euroquol-5D show moderate effects. Thus, the collection of these postoperative scores is sufficient to identify potential high risk patients. Based on a receiver operating characteristic (ROC) analysis, threshold values could be determined for these scores, for which a follow-up examination is recommended.Conclusion Patients who could not achieve functional improvement, pain reduction and improvement in quality of life after implantation of a total hip replacement must be identified at an early stage. The results of our study show that with the help of the Oxford Hip Score and Euroquol-5D, which are answered by the patients three months postoperatively, such high risk patients can be identified. This finding is an added value for the further development of the EndoCert certification system and holistic quality assurance in arthroplasties, while the personnel and time effort remain manageable.Hintergrund Neben klinischen Parametern nimmt auch die subjektive Einschätzung seitens des Patienten zur Bewertung des operativen Ergebnisses einer Endoprothese immer mehr an Bedeutung zu. Mithilfe von Fragenbögen sollen Patienten, die das Behandlungsziel nicht erreicht haben, frühzeitig identifiziert werden, um weitere Interventionen einleiten zu können.Material und Methoden Ein Fragenkatalog, bestehend aus verschiedenen PROMs (Patient-Related Outcome Measurements), wurde prä- und 3 Monate postoperativ von Patienten vervollständigt, die mit einer Hüftendoprothese versorgt wurden. Anschließend erfolgte 12 – 16 Wochen postoperativ eine standardisierte Nachuntersuchung dieser Patienten, nach der festgelegt wurde, ob die Fortsetzung der Therapie erforderlich ist, um das Behandlungsziel zu erreichen. Hierfür wurden verschiedene Konsequenzen definiert.Ergebnisse Es konnten signifikante Unterschiede zwischen den Gruppen der Konsequenzen der Nachuntersuchungen über beide Zeitpunkte, aber auch bei der ausschließlichen Betrachtung der postoperativen Scores, nachgewiesen werden. Zudem zeigen die Korrelationen für die postoperativen Scores und einiger Konsequenzen der klinischen Nachkontrolle für den Oxford Hip Score (OHS), den OHS-Funktionsscore und den Euroquol-5D mittlere Effekte. Somit ist die Erhebung dieser postoperativen Scores ausreichend, um potenzielle Risikopatienten identifizieren zu können. Für diese Scores konnten auf Basis einer ROC-Analyse (ROC: Receiver Operating Characteristic) Schwellenwerte bestimmt werden, ab deren Unterschreitung eine Nachuntersuchung zu empfehlen ist.Schlussfolgerung Patienten, die nach Implantation einer Hüfttotalendoprothese keine Funktionsverbesserung, Schmerzreduktion und Verbesserung der Lebensqualität erreichen konnten, müssen frühzeitig ermittelt werden. Die Ergebnisse unserer Studie zeigen, dass mithilfe des Oxford Scores und des Euroquol-5D, die 3 Monate postoperativ von den Patienten beantwortet werden, solche Risikopatienten identifiziert werden können. Diese Erkenntnis ist für die Weiterentwicklung des EndoCert-Zertifizierungssystems und der ganzheitlichen Qualitätssicherung in der Endoprothetik ein Zugewinn, wobei der personelle und zeitliche Aufwand überschaubar bleibt.
Keywords: EndoCert; follow-up study; hip arthroplasty; Oxford Score; Euroquol-5D